Goldie Blox ruins rules the school! - McAnulty, Stacy (McAnulty, Stacy. Goldie Blox, 2017)
"When Goldie Blox accidentally blows off the roof of her school, she and her friends Val, Ruby, and Li have to work together and use their creative know-how to rebuild the school"--